STATISTICAL PRACTICES IN GENERAL SURGERY RANDOMIZED CONTROL TRIAL STUDY: AN EVALUATION OF PUBLISHED RESEARCH ARTICLES - Dharmendra Kumar Dubey; Nancy Parul (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This review article evaluates the use and appropriateness of statistical methods in general surgery research articles indexed in PubMed over the past five years (2020–2025). A total of 5,388 original articles were screened, among which 15 randomized controlled trials (RCTs) containing the keyword “General Surgery” in the title were identified. These RCTs featured 23 statistical applications primarily focused on continuous or ordinal outcomes, with the Pearson chi-square test and Student’s t-test being the most commonly used methods. Notably, 26% of the reviewed articles showed deviations from CONSORT guidelines or omitted the “General Surgery” keyword, limiting discoverability and methodological clarity. The most frequent statistical error observed was inadequate reporting of p-values. Furthermore, only 33.3% of the studies clearly specified the statistical software used, with SPSS and STATA being the most frequently mentioned programs. An encouraging trend toward the increased and more appropriate use of statistical methods in general surgery literature, indicating growing awareness among researchers. However, the persistence of reporting issues and inconsistent software disclosure highlights the need for improved adherence to reporting